TGH Said Amin's Contribution to the Development of Islamic Education in Bima City - Mujahidin Al Falah; Ilham; Ferdiansyah (Lembaga Bale Literasi, 2026)
This research is motivated by the important role of local religious figures in the development of Islamic education in the region, particularly in Bima City. TGH Said Amin is known as one of the figures who contributed to this field. The purpose of this study is to describe TGH Said Amin's contribution to the development of Islamic education in Bima City and to analyze the supporting and inhibiting factors. The method used is library research, which is research conducted by reviewing various literature sources relevant to the research focus. The approach used in this study is a descriptive qualitative approach. The results of the study show that TGH Said Amin played a role as the founder and developer of Islamic educational institutions such as Islamic boarding schools and madrasas which became centers for the development of morals and knowledge for the young generation of Bima. The teaching method applied is integrative, combining the sorogan and bandongan traditions with modern materials and strengthening Arabic. Intellectual contributions through preaching and training Quran teachers have expanded the impact of education to the wider community. This success is supported by community social capital, government support, and a network of cleric, despite facing constraints such as limited funding and the challenges of modernization. Overall, TGH Said Amin acts as an agent of change, making Islamic education in Bima City more character-based, structured, and relevant to contemporary needs, both in character and adaptive.